Enhancing Energy Efficiency in Libyan Residential Buildings: Selecting Optimal Insulation and Integrating Renewable Energy Technologies - Alkezza, Ayman; Bodalal, Awad; Mashiti, Salah; Aladwli, Omer (Journal of Pure & Applied Sciences, 2025)
The rising electricity demand in Libya, particularly from the residential sector, underscores the urgent need for sustainable energy solutions. This study investigates the potential of integrating energy-saving technologies, including solar water heating systems, photovoltaic (PV) cells, optimized insulation materials, and compact fluorescent lamps (CFLs), to enhance energy efficiency in Libyan households. A comprehensive methodology was employed, combining theoretical analysis and simulation-based evaluations across diverse climatic zones in Libya. Key findings reveal that adopting these integrated technologies can significantly reduce energy consumption, lower greenhouse gas emissions, and achieve considerable cost savings. For instance, optimizing insulation material thickness led to annual energy savings of up to 30% with payback periods between 4 to 6 years, while leveraging Libya’s abundant solar resources further amplified these benefits. This research provides actionable insights for policymakers and stakeholders to promote sustainable practices and reduce the country’s dependence on fossil fuels, aligning with global efforts to combat climate change and enhance energy security.